2002
DOI: 10.1103/physrevb.66.205407
|View full text |Cite
|
Sign up to set email alerts
|

Character of tightly bound excitons in small argon clusters: Insights from size-dependent energy shifts

Abstract: The structure of the first electronically excited states of small Ar M clusters (M р100) embedded in large Ne N (N ϭ7500) clusters is investigated using fluorescence excitation spectroscopy. In the energy range of the characteristic absorption of Ar clusters ͑11.5-12.9 eV͒, surface excitons of Ar clusters embedded in Ne disappear, while additional absorption bands appear. They are assigned to excitons at the interface between the Ar cluster and the Ne host cluster. The observed energy shift of all absorption b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 32 publications
4
33
0
Order By: Relevance
“…4,28 For this second type of exciton, we would not expect the same kind of variation with sizes as for semiconductors but something like the behavior observed in rare gas clusters. 6 Nevertheless the confinement effect we observe is closer to the one on semiconductors as evidenced by Fig. 6.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…4,28 For this second type of exciton, we would not expect the same kind of variation with sizes as for semiconductors but something like the behavior observed in rare gas clusters. 6 Nevertheless the confinement effect we observe is closer to the one on semiconductors as evidenced by Fig. 6.…”
Section: Discussionsupporting
confidence: 49%
“…For this kind of systems we also came to quite good an understanding thanks to extensive work on rare gas clusters ͑see, for instance, Ref. 6 …”
Section: Introductionmentioning
confidence: 99%
“…This observation is understandable because of direct interaction of the Ar excitons with the surrounding Ne atoms which gives rise to a new Ar/ Ne interface absorption band that appears as a shoulder around 12.65 eV. 79,80 The appearance of this band verifies that our initial assumption of complete solvation of the Ar shells inside the Ne cluster and site-independent energy transfer from excitons to O 2 was correct. The Ar/ Ne interface band lies above the O 2 ionization threshold.…”
Section: B Pickup Experimentsmentioning
confidence: 69%
“…The first shell is built of m 1 ϭ12 atoms around one atom in the center. In case of H 2 O-doped Ar clusters, an extraordinary stability of Ar 12 H 2 O has been earlier reported in theoretical work by Liu et al 22 21 ͑for an explanation see the text͒. and 1/e 2 correspond to the size m of ϳ32 and ϳ54.…”
Section: ͑4͒mentioning
confidence: 99%
“…The mean size of the solute Ar m cluster in the cross-beam experiments at CLULU has been previously estimated by Laarmann et al 8 based on theoretical and experimental work by Lewerenz et al 20 It has been shown that the absorption lineshape of the first exciton of the solute Ar m cluster in a large Ne cluster changes with its size m according to a Frenkel exciton model. 21 A comparison of excitation spectra of Ar m @Ne N clusters obtained in our experiments ͑when a water cross-beam is switched off͒ with the results of Ref. 21 allows a cluster size m calibration.…”
Section: ͑4͒mentioning
confidence: 99%